Pembuatan dan Penggunaan Pestisida Nabati Pada Tanaman Hotikultura di Wonorejo Kecamatan Gondangrejo Karanganyar - Kharis Triyono; Sumarmi Sumarmi (LPPM UNINUS, 2020)
The aim of this program to transfer the technology for making vegetable pesticides that can be used by the community directly by making vegetable pesticides from plants that are easily available to the environment, made and used by the community. The targets of this program are the people of Wonorejo Village, especially RW I, who tend to use high synthetic pesticides in controlling pests (plant pests) in horticultural crops. The expected target after this program is that target partners are able to independently make vegetable pesticides by utilizing local plants around them and applying them directly to their agricultural land the Using of local plants as vegetable pesticides will be able to reduce agricultural production costs which have an impact on increasing farmers' income. will reduce the use of synthetic pesticides and save the environment, as well as increase the economic value of crops and in the future will increase income for farmers/ communities, which in turn can improve the welfare of the community. The methods used to achieve the targets in this program are 1) Counseling/lectures, practice, and coaching. The materials included introducing vegetable pesticides and some plants that can be used as sources of vegetable pesticides and the impact of using synthetic pesticides in the long term and some cases of resistance 2). Direct practice on how to manufacture vegetable pesticides and their use. The implementation of activities is carried out in the following stages: preparation (coordination with community leaders and related agencies who assist) implementation includes socialization, training, and manufacture of vegetable pesticides, the practice of making vegetable pesticides, coaching with direct application assistance activities in the field.